Mediatized vernacularization: On the structure, entextualization and resemiotization of Varoufakiology. (December 2016) - Theodoropoulou, Irene
Abstract: This paper focuses on the structure of mediatized discourses on the former Greek minister of finance Yanis Varoufakis, which are labeled Varoufakiology. Through a multimodal discourse analysis of cartoons and photographs, which have been collected systematically in social and mainstream media through hypermedia ethnography, it is argued that neolectal stylistic features, including body posture, clothing and negotiation style are the emerging themes that prevail in mediatized communication with and about Varoufakis. In unison, they create a sense of semiotic vernacularization, translated into interacting linguistic and semiotic simplification, boldness and unconventionality associated with a controversial and multidimensional personality with intense and impactful political, academic and popular activity. In this sense, the overall argument put forward is that this mediatized vernacularization is not only a linguistic but also a widely semiotic type of communication, which reframes and positions Varoufakis as a political leader brought to light through controversial aspects of his identity, leadership and politics. Highlights: Discourses pertaining to Yanis Varoufakis include body posture, clothing and negotiation style. Varoufakis׳ unconventional identity highlights political controversies in Greece. Semiotic vernacularization is a dimension of mediatized communication. Entextualization and resemiotization create digitally prosumed humorous memes. Hypermedia ethnography is a suitable method to investigate digital multimodal data.